2017
DOI: 10.17659/01.2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

Transvascular Growth of Hepatocellular Carcinoma

Abstract: Background: Cardiac tumors may be primary (benign or malignant) or metastatic (malignant). They can cause inflow-outflow tract obstruction, thromboembolism, arrhythmias, or pericardial disorders. Case Report: A 30 year old male presented with cough and dyspnea of one month duration. Routine echocardiography revealed a large tumor mass filling the entire right atrium. Computed tomography delineated tumor arising from the left lobe of the liver and entering through the inferior vena cava (IVC) to right atrium. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…A study by Jun CH et al [13] identified some risk factors for RA extension in a cohort of 665 patients diagnosed with HCC (33 with RA invasion), namely a modified TNM staging classification ≥IVa, hepatic vein invasion, concomitant PV and IVC invasion, and multinodular HCC. The initial investigation of choice to detect cardiac metastasis is twodimensional transthoracic echocardiography, as it is noninvasive and both pericardial involvement and intra-cavitary lesions can be detected with high sensitivity [14].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jun CH et al [13] identified some risk factors for RA extension in a cohort of 665 patients diagnosed with HCC (33 with RA invasion), namely a modified TNM staging classification ≥IVa, hepatic vein invasion, concomitant PV and IVC invasion, and multinodular HCC. The initial investigation of choice to detect cardiac metastasis is twodimensional transthoracic echocardiography, as it is noninvasive and both pericardial involvement and intra-cavitary lesions can be detected with high sensitivity [14].…”
Section: Discussionmentioning
confidence: 99%